CORRELATING TEACHERS’ DIGITAL ATTITUDES AND KNOWLEDGE TRANSFER IN THE INTERMEDIATE LEVEL - Eusebio, John Paul P. (President University, 2024)
This study aimed to determine the level of teachers’ digital attitudes and knowledge transfer of 187 randomly selected public elementary school teachers in the intermediate level in the District of Sapian for S.Y. 2023-2024. Significant related foreign and local literatures about digital attitudes and knowledge transfer were cited. Descriptive-correlational research design was utilized. A validated and reliability tested researcher-made questionnaire was used to gather the data needed. Statistics IBM 28 program was used to analyse and interpret data using frequency count, percentage, mean, t-test, analysis of variance and Pearson r. The findings of the study revealed that the levels of both teachers’ digital attitudes in terms of perceived influence, control and response; and knowledge transfer in terms of explicit, implicit and tacit were very high. Significant differences were found on teachers’ digital attitudes when they were grouped according to their sex, but age and number of ICT trainings attended were insignificant. Significant differences were found on teachers’ knowledge transfer when they were grouped according to sex, however insignificant difference existed in terms of age and number of ICT trainings attended. The level of teachers’ digital attitudes and the level of knowledge transfer of teachers were significantly related. It implies that there is a relationship between teacher’s digital attitudes and on how they transfer knowledge pupils, peers and significant others.